Renal Function and Body Mass Index Contribute to Serum Neurofilament Light Chain Levels in Elderly Patients With Atrial Fibrillation - Polymeris, Alexandros A.; Helfenstein, Fabrice; Benkert, Pascal; Aeschbacher, Stefanie; Leppert, David; Coslovsky, Michael; Willemse, Eline; Schaedelin, Sabine; Blum, Manuel R.; Rodondi, Nicolas; Reichlin, Tobias; Moschovitis, Giorgio; et al. (Frontiers in Neuroscience, 2022)
Objective: Serum neurofilament light chain (sNfL) is increasingly used as a neuro-axonal injury biomarker in the elderly. Besides age, little is known about how other physiological factors like renal function and body mass index (BMI) alter its levels. Here, we investigated the association of estimated glomerular filtration rate (eGFR) and BMI with sNfL in a large sample of elderly atrial fibrillation (AF) patients. Methods: This is a cross-sectional analysis from the Swiss-AF Cohort (NCT02105844). We measured sNfL using an ultrasensitive single-molecule array assay. We calculated eGFR using the Chronic-Kidney-Disease-Epidemiology-Collaboration creatinine (eGFRcrea) and creatinine-cystatin C (eGFRcrea-cys) formulas, and BMI from weight and height measurements. We evaluated the role of eGFR and BMI as determinants of sNfL levels using multivariable linear regression and the adjusted R2 (R2adj). Results: Among 2,277 Swiss-AF participants (mean age 73.3 years), eGFRcrea showed an inverse curvilinear association with sNfL after adjustment for age and cardiovascular comorbidities. BMI also showed an independent, inverse linear association with sNfL. The R2adj of models with age, eGFRcrea and BMI alone was 0.26, 0.35 and 0.02, respectively. A model with age and eGFRcrea combined explained 45% of the sNfL variance. Sensitivity analyses (i)further adjusting for vascular brain lesions (N=1,402 participants with MRI) and (ii)using eGFRcrea-cys yielded consistent results. Interpretation: In an elderly AF cohort, both renal function and BMI were associated with sNfL, but only renal function explained a substantial proportion of the sNfL variance. This should be taken into account when using sNfL in elderly patients or patients with cardiovascular disease.